2009
DOI: 10.1507/endocrj.k09e-224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Genes During Proliferative Response of the Liver Induced by Follistatin

Abstract: Abstract. the liver mass is controlled strictly and maintained constant in normal and pathological situations. an exception is observed after an administration of follistatin, which induces proliferation in intact liver. In the present study, we identified genes differentially expressed in proliferating liver caused by overexpression of follistatin-288. Adenovirus vector encoding follistatin-288 (Ad-FS) or green fluorescent protein was injected intraperitoneally in rats. Changes in the liver weight, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Many studies of the biologic activity of this protein have been limited to gene therapy approaches using adeno-associated viral delivery (Takabe et al, 2003;Kota et al, 2009;Medina et al, 2009;Foley et al, 2010). These investigations have shown that follistatin has potent antiinflammatory activities, wound-healing properties, and muscle hypertrophy and hyperplasia-stimulating effects in rodents and nonhuman primates (Kogure et al, 1995;Wankell et al, 2001;Fuwii et al, 2005;Fumagalli et al, 2007;Tsuchida, 2008;Zimber et al, 2011;de Kretser et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies of the biologic activity of this protein have been limited to gene therapy approaches using adeno-associated viral delivery (Takabe et al, 2003;Kota et al, 2009;Medina et al, 2009;Foley et al, 2010). These investigations have shown that follistatin has potent antiinflammatory activities, wound-healing properties, and muscle hypertrophy and hyperplasia-stimulating effects in rodents and nonhuman primates (Kogure et al, 1995;Wankell et al, 2001;Fuwii et al, 2005;Fumagalli et al, 2007;Tsuchida, 2008;Zimber et al, 2011;de Kretser et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported potent beneficial effects of follistatin administration in various indications, such as inflammation, liver repair, fibrosis, wound healing, hair regrowth, and muscle disorders, including muscular dystrophy (Kogure et al, 1995;Wankell et al, 2001;Fuwii et al, 2005;Fumagalli et al, 2007;Tsuchida, 2008;Zimber et al, 2011;de Kretser et al, 2012). Many of these disorders require systemic wide pharmacological effects, and as a result, several groups have focused on the use of gene therapy in the form of adeno-associated virus to obtain protein exposure levels required for activity in animal models of disease (Takabe et al, 2003;Kota et al, 2009;Medina et al, 2009;Foley et al, 2010). These studies have yielded promising proof-ofconcept data for the therapeutic potential for follistatin; however, from a practical perspective, the use of follistatinadeno-associated virus as a bona fide human therapeutic is squelched by a tenuous clinical and regulatory path.…”
Section: Introductionmentioning
confidence: 99%